Dialectical behavior therapy with American Indian/Alaska Native adolescents diagnosed with substance use disorders: Combining an evidence based treatment with cultural, traditional, and spiritual beliefs. (December 2015) - Beckstead, D. Joel; Lambert, Michael J.; DuBose, Anthony P.; Linehan, Marsha
Abstract: This pilot study examined pre to post-change of patients in a substance use residential treatment center that incorporated Dialectical Behavior Therapy with specific cultural, traditional and spiritual practices for American Indian/Alaska Native adolescents. Specifically, the incorporation of cultural, spiritual and traditional practices was done while still maintaining fidelity to the evidence based treatment (DBT). 229 adolescents participated in the study and were given the Youth Outcome Questionnaire-Self-Report version at pre-treatment and post-treatment and the total scores were compared. The results of the research study showed that 96% of adolescents were either "recovered" or "improved" using clinical significant change criteria. Additionally, differences between the group's pre-test scores and post-test scores were statistically significant using a matched standard T-test comparison. Finally, the effect size that was calculated using Cohen's criteria was found to be large. The results are discussed in terms of the implication for integrating western and traditional based methods of care in addressing substance use disorders and other mental health disorders with American Indian/Alaska Native adolescents. Highlights: The first investigation of the use of DBT with this population (AI/AN) 96% of adolescents were recovered using clinical significant change criteria. The effect size of treatment was large, using Cohen's d (d = 1.315). Paired, two-tailed T-Test yielded a P value that was less than 0.0001. Significant positive outcomes blending cultural, traditional practice with DBT